Finding and Counting Difficult to Reach Population Groups in the UK (and other Developed Countries) - Carr-Hill, Roy (International Journal of Population Data Science, 2018)
Background Censuses are meant to provide a complete count and basic information about all households and individuals in a country. After decades of complacency, it has begun to be realised that this can no longer be guaranteed. Several of the presentations at the Edinburgh in March 2018 demonstrated methods which the ONS were developing to resolve many of the problems; but those methods do not solve the problem of those who, for a variety of reasons, cannot or do not want to be counted. Objectives This paper sets out to document the possible size of the ‘hidden’ populations in the UK and demonstrate that they are predominantly poor. Methods (including data) Estimates of the numbers are provided (globally and in the UK) in difficult-to-reach categories: homeless/street children, care homes/hospitals, military, prisons, refugees and illegal immigrants, gypsies/travellers, urban slums. With the exception of the military, the majority in each group are poor. Findings The paper then reviews approaches to counting and describing the various categories: grosso modo, those in institutions can already be headcounted but apart from relevant institutional status, gender and perhaps age, we have no other information about them; but the main problem is that, in many cases, there is potential double counting with their (temporarily) broken household. for both Refugees/ Illegal immigrants and Gypsy/ Traveller Population, the main problem is the reluctance of the former to complete forms or be interviewed and of the latter to acknowledge their own ethnic identity in high rise blocks where lifts are not always working, there will certainly be some unsurveyed and uncensored people; and the Grenfell Towers experience shows that there is not always a secure count of the numbers Conclusions The issue of ‘hidden’ or missing populations in the UK has to be taken much more seriously.